MILK PRODUCTIVITY OF SIMMENTAL COWS DURING DIFFERENT STAGES OF LACTATION UNDER THE INFLUENCE OF VILOFOSS FEED SUPPLEMENT (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the effects of the feed supplement Vilifoss on the milk productivity of Simmental cows during different stages of lactation. The cows were divided into three groups, and the supplement was administered at the beginning, middle, and end of lactation. The results showed that Vilifoss significantly increased overall milk yield and improved milk fat and protein content. The highest productivity was observed when Vilifoss was administered during the mid-lactation period. Additionally, positive effects on cow health, appetite, and metabolic activity were noted. These findings suggest that targeted use of Vilifoss can be an effective strategy to enhance dairy productivity in Simmental cows.